Luteinizing Hormone Contributes to Fetal Tolerance by Regulating Adaptive Immune Responses. (5th March 2014) - Schumacher, Anne; Poloski, Eileen; Spörke, Dominique; Zenclussen, Ana C.
<x xml:space="preserve">Abstract</x> Problem Pregnancy hormones were proposed to be crucially involved in fetal tolerance. Recently, we showed that human chorionic gonadotropin (hCG) not only increases the number and activity of regulatory T cells (Treg) but also retains tolerogenic dendritic cells (DCs). Here, we investigate whether the highly homologous luteinizing hormone (LH) modulates Treg number and DC phenotype and thereby supports pregnancy. Method of study Abortion‐prone females were treated with LH or PBS on different gestation days. Pregnancy outcome and the number and phenotype of Treg and DCs were evaluated in the periphery and locally. Results We discovered that LH application completely prevented fetal rejection in abortion‐prone females. This protective effect was associated with a Treg augmentation peripherally and locally. Moreover, LH reduced the number of total and mature DCs. Conclusion Our data suggest that LH, similar to hCG, is involved in the regulation of adaptive immune responses, thus contributing to fetal tolerance.